Collier's Encyclopedia with Bibliography and Index: Volume 22: Synge to Uruguay - Bernard Johnston; William D. Halsey (New York Macmillan Educational Company, 1991)
Editorial Director: William D. Halsey Editor in Chief: Bernard Johnston . 24 volumes : illustrations (part color) maps (part color) portraits
Collier Macmillan Canada Toronto . Maxwell Macmillan International Publishing Group New York- Oxford- Singapore- Sydney
Vol. 24: Bibliography and index
Keywords: Encyclopedias (3GdehShYGJs; Encyclopedias and dictionaries; General; Bibliography